Hubungan Perilaku Ibu, Peran Nakes, Dan Motivasi Keluarga Terhadap Kejadian Anemia Pada Ibu Hamil Di Desa Permis : The Relationship Between Maternal Behavior, the Role of Health Workers, and Family Motivation on the Occurrence of Anemia in Pregnant Women in Permis Village - Sulasmi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Anemia in pregnancy is a problem in the health sector because it is an indicator of poor nutritional status and health status. Anemia during pregnancy is defined as Hb less than 10 g/dL. If Hb is below 12 g/dL in early pregnancy, pregnant women may need to be given prophylactic drugs because of hemodilution which reduces Hb levels to less than 10 g/dL. The purpose of this study was to determine the relationship between maternal behavior, the role of health workers, and family motivation on the incidence of anemia in pregnant women in Permis Village in 2022. Methods: This type of research is an analytical descriptive study using a quantitative method with a cross-sectional approach. Results: The statistical test results show that there is a relationship between the role of midwives and the incidence of anemia in pregnant women in Permis Village in 2022 with a p-value of 0.006. there is a relationship between family motivation and the incidence of anemia in pregnant women in Permis Village in 2022 with a p-value of 0,021. there is a relationship between anemia prevention behavior and the incidence of anemia in pregnant women in Permis Village in 2022 with a p-value of 0.013. Discussion: The conclusion is the relationship between maternal behavior, the role of health workers, and family motivation toward the incidence of anemia in pregnant women in Permis Village in 2022. The suggestion for this research is to apply healthy behavior on how to prevent and treat anemia during pregnancy to prevent complications in pregnant women and fetuses.